PERANCANGAN PROMOSI WISATA ALAM LEMBAH HARAU KABUPATEN LIMA PULUH KOTA - Andri Arizka, Drs. Syafwandi, M.Sn, Dra. Minarsih, M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2013)
The purpose of this booklet media design are (1) As a media campaign to introduce harau valley in the Kabupaten Lima Puluh Kota, (2) Increase visitors who come to tour the harau valley, (3) Creating a promotional media tour in booklet form, (4) Realizing the existence of a media campaign harau valley more communicative, Based on these conditions, the writer makes the a Booklet, Note Book, Kalender, Stiker, X-Bunner, Wall Clock, T-shirt, Flayer, Pin, Key Chain, Mug. Keywords: Promotion, Media Print, Booklet, Harau Valley